The Effect of Health Literacy Level on the Use of E-Health Applications - Ozan, Derviş; Kiliç, Mahmut (International Journal of Statistics in Medical Research, 2023)
Purpose: The purpose of the study is to measure the effect of health literacy (HL) level on the level of use of e-health applications among public employees, excluding health workers serving directly to the public and working in public institutions in the downtown area of Yozgat, Turkey. Methods: The study is cross-sectional and was conducted in 2021 among public employees. 476 public personnel working in state institutions in the city center participated in the study. Chi-square test, t-test, ANOVA, and multinomial logistic regression were used to evaluate the data. Results: Of the participants, 64.3% of them were male, 74.9% were married, 45.3% were in the 30-39 age group, and 60.9% were undergraduates. It was observed that 21.5% of the people in the research group had insufficient health literacy (SSL), 41.3% were problematic and 37.2% were sufficient. It was seen that the most used E-health application was E-pulse with 84.9%, followed by Life Fits into Home (LFH) and Central Physician Appointment System (CPAS) (64.3%), and the lowest was the hospitals’ online systems (29.1%). The use of E-Nabız (e-Pulse) and E-Devlet (e-Government) SSI applications according to HL level was not found to be statistically significant (p>0.05). Conclusion: The vast majority of public employees use E-Pulse, and approximately 2/3 of them use LFH and CPAS. Less than half of the participants in the study had a sufficient health-literacy level, and the effect on e-Health practices was not found significant.